(untitled) (Journal of Contemporary Issues in Accounting, 2026)
This study investigated the effect of XBRL adoption and digital financial reporting on financial statement comparability among listed Nigerian deposit money banks. The study employed a cross-sectional survey design to collect data from 316 respondents. Descriptive statistics and simple linear regression were employed for data analysis. Results indicated that XBRL adoption has a significant positive effect on financial statement, IT infrastructure also exerts a positive and significant effect. Bank size positively influences comparability, indicating that larger institutions are better positioned to implement digital reporting initiatives. In all XBRL adoption significantly enhances financial reporting comparability among Nigerian deposit money banks. The findings highlight the strategic importance of XBRL adoption, robust IT infrastructure, and institutional capacity in enhancing the transparency, reliability, and comparability of financial statements in the Nigerian deposit money banks.